Credence in the Organization’s Ability to Respond to Change – Implications on Work Engagement and Job Satisfaction in the Church of Sweden - Edvik, Anders; Geisler, Martin; Muhonen, Tuija; Witmer, Hope; Björk, Josefin (Frontiers in Psychology, 2020)
As part of society, religious organizations are exposed to contextual conditions and challenges. However, adapting to external conditions is an act of balance since too much compromising may risk having a negative effect on employees’ perception of organizational authenticity and, in turn, employees’ well-being and attitudes toward work. In this study, we examined how specific characteristics of the work, in terms of job demands (role conflict and emotional demands) and job resources (influence at work and social community at work), as well as employees’ credence in the organization’s ability to respond to change, relate to employee well-being within the Church of Sweden. In total 2,112 employees (58% participation rate) answered a web-based survey. The results of regression analyses showed that job resources and credence in the organization’s ability to respond to change provided a clear contribution to the explanation of variance in work engagement and, especially, job satisfaction. However, the contribution of job demands was less clear. Moreover, to further the understanding of the association between employees’ credence in the organization’s ability to respond to change and employee well-being, the mediating effect of job resources was tested. The results showed that the association between credence and well-being is in part mediated by job resources. In sum, the study demonstrate that employees’ credence in the organization’s ability to respond to change is important to consider for understanding employee well-being within religious organizations. In conclusion, our study suggest that organizations that are built up on strong values and institutionalized beliefs, such as religious and faith-based organizations, need to tread carefully in the process of adapting to conformal pressure for change. This, since the actions and choices of the organization are important for employees’ credence in the organization and, in turn, employee well-being. Implications and recommendations for future research are discussed.